Mediating Effects of Empathy on Competence of Korean Nursing Students - Han-Gyo Choi; Hye-Jin Kim; Sunhee Lee (Tehran University of Medical Sciences, 2021)
Background: Empathic communication is important for nurses to establish therapeutic relationships with patients and to improve the quality of care. Thus, empathy is essential for nursing students who will be future nurses. The aim of this study was to examine the mediating role of empathy in the influence of communication competence on interpersonal competence of nursing students. Methods: This study was conducted at the Catholic University of Korea. Participants were 218 nursing students who completed a survey questionnaire on general characteristics, Interpersonal Reactivity Index, Primary Communication Inventory, and Interpersonal Competence Questionnaire from Feb. 20 to Feb. 21, 2014. Data were analyzed using simple and multiple regression analyses. Mediation analysis was performed according to the Baron and Kenny method and Sobel test. Results: A three-step regression analysis was performed to verify the mediating role of empathy in the relationship between communication competence and interpersonal competence. Results confirmed that communication competence significantly influenced interpersonal competence, showing that empathy had a partial mediating role (Z=2.40, P=.016). Conclusion: Communication competence improved interpersonal competence through mediation by empathy in nursing students. Result of this study suggested that nursing schools should implement communication education that can strengthen empathy in order to boost nursing students' interpersonal competence.